1984
DOI: 10.1002/recl.19841030101
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the chemical conversion of glucose

Abstract: A . P. G . Kieboom et al. /Aspects of the chemical conversion of glucosecarbohydrate chemistry. Moreover, there is still substantial progress in the science and technology of non--enzymic procedures, which are more generally applicable than enzymatic isomerizations. For instance, the industrial isomerization of lactose into lactulose occurs in aqueous medium with base as the catalyst334, since there is no enzyme system developed as yet for this conversion. The classical paper of Lobry de Bruyn and Alberda van … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…It was fortunate that Butlerow 39 did not use completely purified formaldehyde to initiate the reaction, because the formation of sugars from formaldehyde is dependent on the presence of trace amounts of one of several common impurities. 43,44 Glycolaldehyde, the first product of the polymerization reaction, is an efficient initiator and is often added to get the formose reaction started. In the absence of an initiator, formaldehyde in alkaline solution undergoes the Cannizzaro reaction, yielding methanol and formic acid.…”
Section: Formose Reactionas a Primary Prebiotic Source Of Ribosementioning
confidence: 99%
See 1 more Smart Citation
“…It was fortunate that Butlerow 39 did not use completely purified formaldehyde to initiate the reaction, because the formation of sugars from formaldehyde is dependent on the presence of trace amounts of one of several common impurities. 43,44 Glycolaldehyde, the first product of the polymerization reaction, is an efficient initiator and is often added to get the formose reaction started. In the absence of an initiator, formaldehyde in alkaline solution undergoes the Cannizzaro reaction, yielding methanol and formic acid.…”
Section: Formose Reactionas a Primary Prebiotic Source Of Ribosementioning
confidence: 99%
“…In this mechanism, glycolaldehyde is formed from formaldehyde (by a still undefined mechanism) initiating an autocatalytic cycle producing more glycolaldehyde, resulting in a rapid consumption of HCHO to yield carbohydrates as intermediates on the way to more complex mixtures (Figure ). It was fortunate that Butlerow did not use completely purified formaldehyde to initiate the reaction, because the formation of sugars from formaldehyde is dependent on the presence of trace amounts of one of several common impurities. , Glycolaldehyde, the first product of the polymerization reaction, is an efficient initiator and is often added to get the formose reaction started. In the absence of an initiator, formaldehyde in alkaline solution undergoes the Cannizzaro reaction, yielding methanol and formic acid .…”
Section: Abiotic Synthesis Of Sugars (Ribose/2-deoxyribose)mentioning
confidence: 99%
“…Generally, strong inorganic bases (e.g., calcium hydroxide) have been shown to be favorable for converting glucose to retro-aldolization byproducts via cation–ketose complexes, thus giving a poor yield of fructose (below 10%). , In alkaline medium, borate could partly protect monosaccharides against base degradation by forming a borate ester complex; concurrently, the presence of divalent calcium was demonstrated to increase sugar retro-aldolization . The alkaline degradation of either d -fructose, d -glucose, or d -mannose was found to occur in an irreversible pathway to yield carboxylic acid products such as lactic acid, glycolic acid, and formic acid under these studied reaction conditions. In contrast, amines possessing a broad range of p K a values were unable to form cation–ketose complexes, which offered potentially more flexibility to optimize the fructose selectivity. Liu et al found that organic amines (e.g., morpholine, piperazine, ethylenediamine, triethylamine, piperidine, and pyrrolidine with p K a of 8.4–11.3) afforded moderate glucose conversions (43–62%) with improved fructose yields (17–31%) in water after 30 min at 100 °C (Table , entry 4) .…”
Section: Homogeneous Chemo-catalysismentioning
confidence: 99%
“…It has proven to be an excellent option for different biomass chemical valorization processes, including the hydrodeoxygenation of lignin-derived aromatics, polysaccharide hydrogenolysis, or the reduction of platform molecules . CTH has also been explored in the transformation of glucose to sorbitol, although reported results are scarce, compared to hydrogenation, and evidence a low performance in terms of sorbitol productivity. In addition, the reducing nature of glucose makes its disproportionation easy under the reported CTH reaction conditions. , Enhancing the productivity of glucose to sorbitol CTH requires using hydrogen donors from which hydrogen abstraction is easier as compared to glucose or at least using reaction conditions favoring so.…”
Section: Introductionmentioning
confidence: 99%